Effect of Digitalization of Web-Based Science Learning Media with the STEAM Approach to Student's Creative Thinking Abilities - Rilexen S P Mulder, Wilem; Syaipul Hayat, Muhammad; Khoiri, Nur (KnE Social Sciences, 2024)
Learning innovation in the present digital transformation era emphasizes employing technology and methods in learning. The utilization aims to enhance 21st-century foundational skills, including students’ abilities in creative thinking. This research was conducted with the purpose of investigating how the application of web-based science learning media with the Science, Technology, Engineering, Mathematics, and Arts (STEAM) approach improves student’s creative thinking abilities. This research process uses a quasi-experimental research design using a one-group pretest-posttest design. The sample of this research consisted of 7th-grade students at SMP Negeri 65 Central Maluku. The results showed that website for science learning media with the STEAM approach had a significant impact on student’s creative thinking abilities with very creative indicators of 18.75%, creative 75%, and creative enough of 6.25% with an N-Gain Test score of 0.61 in the medium category and by results of data analysis of the t-test with a significance value (2-tailed) 0.000 < 0.05. based on research results, using web-based science learning media with the STEAM approach can potentially increase student’s ability to think creatively by integrating the media flow of science, technology, engineering, art, and mathematics. With this media, teachers can train students to produce innovative solutions and creative thinking skills and support digital transformation. Keywords: STEAM, media, creative thinking, web-based learning